Conscious Sedation with Inhaled 50% Nitrous Oxide/Oxygen Premix in Photodynamic Therapy Sessions for Vulvar Lichen Sclerosus Treatment - Cabete, J (2015)
Photodynamic therapy has been described as an effective therapeutic option in selected cases of anogenital lichen sclerosus that are refractory to first-line treatments. However, procedure-related pain is a limiting factor in patient adherence to treatment. The authors report the case of a 75-year-old woman with highly symptomatic vulvar lichen sclerosus, successfully treated with photodynamic therapy. An inhaled 50% nitrous oxide/oxygen premix was administered during sessions, producing a pain-relieving, anxiolytic, and sedative effect without loss of consciousness. This ready-to-use gas mixture may be a well-tolerated and accepted alternative to classical anesthetics in Photodynamic therapy, facilitating patients' adherence to illumination of pain-prone areas.